Soft-tissue release for hip subluxation and dislocation in cerebral palsy - Takeuchi, Ryoko (J Rural Med, 2017)
Objective: This study aimed to evaluate the effectiveness of soft-tissue release on hip subluxation and dislocation in cerebral palsy as well as activities of daily living after surgery. Patients and Methods: Soft-tissue release was performed in 13 patients (19 hips) with cerebral palsy. Of them, 10 had spastic quadriplegia and three had spastic diplegia. Mean ages were 8.6 years at surgery and 13.8 years at the last investigation. The mean follow-up period was 5.2 years. Hip subluxation and dislocation severities were analyzed before and after surgery and at the final investigation as migration percentage on radiographs. Postoperative activities of daily living were also evaluated in 12 patients. Results: Seven hips classified as mild and moderate preoperatively were classified as good, mild, and moderate at the last investigation. Nine of 12 hips classified as severe preoperatively continued to be severe at the last investigation. However, three of 12 hips classified as severe preoperatively improved at the last investigation. There was a positive correlation between preoperative migration percentage and that at the last investigation. Daily activities improved postoperatively in 12 patients. Conclusions: Early treatment is necessary to prevent hip dislocation and improve hip subluxation. However, several patients with severe subluxation might experience improvement with soft-tissue release alone. Soft-tissue release is effective for treating hip dislocation and subluxation in cerebral palsy and improving daily activities.